Tinjauan Sistem Pengelolaan Sampah Rumah Tangga di Kelurahan Oesapa Kota Kupang - Mince Mb. Atahau; Yendris K. Syamruth; Mustakim Sahdan; Marylin S. Junias (Yayasan Pendidikan Penelitian Pengabdian Algero, 2026)
Waste management based on Law Number 18 of 2008 is a systematic, comprehensive and continuous activity that includes reduction and handling. This study aims to determine the Review of the Household Waste Management System in Oesapa Village, Kupang City. This type of research is descriptive research with a survey method. This research was conducted in Oesapa Village, Kupang City in March-April 2023. The population in this study were all heads of families in Oesapa Village, totaling 8,630 families. The sample in this study was 98 families. The sampling technique in this study used the simple random sampling technique. Data collection using a questionnaire. The data obtained in this study were analyzed descriptively, the presentation of the data was described in the form of a diagram. The results of the study showed that the number respondents based on waste sorting were more in the sufficient category (46%), respondents based on waste collection were more in the less category (54%), respondents based on waste transportation were more in the good category (52%) and respondents based on waste management were more in the less category (36%). It is hoped that the peoplen of Oesapa Subdistrict will dispose of household waste at a temporary disposal site (TPS) because managing their own waste such as burning it can pollute the surrounding environment.